2015
DOI: 10.1159/000441344
|View full text |Cite
|
Sign up to set email alerts
|

Impact of p16 Alterations and Pretreatment Anemia on Toxicity in Head and Neck Cancer Patients Undergoing Definitive Radiochemotherapy

Abstract: Background: Human papilloma virus (HPV) infection, p16 expression and hypoxia may play important roles in the carcinogenesis, treatment response and toxicities of head and neck squamous cell carcinoma (HNSCC). The aim of this analysis was to assess whether there is any correlation between pre-radiotherapy (RT) anemia, p16 expression and toxicities and local control for patients undergoing definitive therapy. Methods: 79 HNSCC patients who had undergone radiochemotherapy (RCT) or RT-antibody therapy were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…This subset of patients is likely to be those undergoing unilateral radiotherapy treatment and, therefore, not identified as a high‐risk patient who receives bilateral treatment. This finding of positive p16 status increasing the need for proactive gastrostomy may be explained by other studies that have reported that patients with p16‐positive disease have higher acute toxicity than p16‐negative disease, and rates of dysphagia and organ toxicity are higher in patients with p16‐positive disease . We also found that current smoking status had an association with the need for a proactive gastrostomy, which is in line with other studies .…”
Section: Discussionsupporting
confidence: 91%
“…This subset of patients is likely to be those undergoing unilateral radiotherapy treatment and, therefore, not identified as a high‐risk patient who receives bilateral treatment. This finding of positive p16 status increasing the need for proactive gastrostomy may be explained by other studies that have reported that patients with p16‐positive disease have higher acute toxicity than p16‐negative disease, and rates of dysphagia and organ toxicity are higher in patients with p16‐positive disease . We also found that current smoking status had an association with the need for a proactive gastrostomy, which is in line with other studies .…”
Section: Discussionsupporting
confidence: 91%
“…Neither has it demonstrated OM progression to be correlated with hemoglobin level before RTH. Such correlation was found by Becker-Schiebe et al [ 36 ]. They confirmed that OM was observed less often in patients with pretreatment anemia, while p16 expression was significantly associated with severe OM [ 36 ].…”
Section: Discussionsupporting
confidence: 82%
“…19,20 Survival and radiobiological studies are therefore needed, ideally, grouping tumour cases by factors that affect patient response to radiation such as: general health status, living habits, normal tissues and tumour biological parameters, tumour microenvironment features etc. [20][21][22][23] Doseresponse models on tumour response to radiation certainly need to be investigated more.…”
Section: Variablesmentioning
confidence: 99%